Poverty Effect and Population Density Towards the Quality of Fishermen's Settlement Environment in Kusamba - Nugraha, I Made Gde Dwiartha; Paturusi, Syamsul Alam; Putra, Dewa Gede Agung Diasana (ASTONJADRO, 2023)
Many people can not live in a house with a quality environment that is livable. The main problem that becomes an obstacle is the economic factor, namely poverty. The poor are forced to live in a bad environment or can live in a good environment but cannot maintain it. The inability of the poor to set aside income to finance environmental maintenance is the main cause of continued environmental degradation. In addition to the problem of poverty, the availability of land is increasingly unable to accommodate population growth, resulting in an environment with a high population density. This problem is very common in settlements in coastal areas. Therefore, research on coastal areas, especially residential areas, is important to do. The purpose of this study was to determine the cause of the decline in the quality of the settlement environment by using the Kumba fisherman settlement as the research location. The method used in this study is a quantitative method with multiple linear regression analysis. Where, the independent variables are poverty and population density, while the dependent variable is environmental quality. From this study, it was found that the poverty factor with several indicators had a significant effect on environmental quality. The comparison of the amount of agricultural land to the population has a significant effect on environmental quality, beating the value of population density which compares the total land area with the total population. This shows the large role of open land used by agricultural activities on the quality of the residential environment.